198k views
5 votes
Keisha solved the following equation: 4x − 2x + 8 = 6(x + 4) Step Work Justification 1 2x + 8 = 6(x + 4) Combine like terms 2 2x + 8 = 6x + 24 Associative property of multiplication 3 −4x + 8 = 24 Subtraction property of equality 4 −4x = 16 Addition property of equality 5 x = −4 Division property of equality

1 Answer

3 votes

4x - 2x + 8 = 6(x + 4) Given

(4x - 2x) + 8 = 6(x + 4)

2x + 8 = 6(x + 4) Combine like terms

2x + 8 = (6)(x) + (6)(4)

2x + 8 = 6x + 24 Distributive Property

2x - 6x + 8 = 6x - 6x + 24

-4x + 8 = 24 Subtraction Property of Equality

-4x + 8 - 8 = 24 - 8

-4x = 16 Subtraction Property of Equality

-4x : (-4) = 16 : (-4)

x = -4 Division Property of Equality


User Fithu
by
5.7k points